Developing Instructional Material of Teaching Grammar Through Moodle to English Education Department Students of Universitas Muhammadiyah Makassar - Ahmad Muhajir; Andi Tenri Ampa; Bahrun Amin (Journal of Development Research, 2022)
This research aims at developing instructional material for English grammar through Moodle at UNISMUH Makassar. it tries to develop the material by identifying students’ need in learning grammar, to describe instructional material of English grammar through Moodle. This research and development (R&D) is conducted by adapting ASSURE models which consist of Analyze, State Objective, Select, Utilize, Require, and Evaluation.The data were gained through questionnaire, the questionnaire is employed to do need analysis to get students’ need in instructional material, and to describe instructional material.meanwhile, questionnaire for validator to conduct development evaluation. Finally, the product of the study is Instructional material of teaching grammar through Moodle